TRPV4 Inhibition Improved Myelination and Reduced Glia Reactivity and Inflammation in a Cuprizone-Induced Mouse Model of Demyelination - Liu, Meiying; Liu, Xuan; Wang, Lei; Wang, Yu; Dong, Fuxing; Wu, Jian; Qu, Xuebin; Liu, Yanan; Liu, Zhian; Fan, Hongbin; Yao, Ruiqin (Frontiers in Cellular Neuroscience, 2018)
The inhibition of demyelination and the promotion of remyelination are both considerable challenges in the therapeutic process for many central nervous system (CNS) diseases. Increasing evidence has demonstrated that neuroglial activation and neuroinflammation are responsible for myelin sheath damage during demyelinating disorders. It has been revealed that the nonselective cation channel transient receptor potential vanilloid 4 (TRPV4) profoundly affects a variety of physiological processes, including inflammation. However, its roles and mechanisms in demyelination have remained unclear. Here, for the first time, we found that there was a significant increase in TRPV4 in the corpus callosum in a demyelinated mouse model induced by cuprizone (CPZ). RN-1734, a TRPV4-antagonist,clearly alleviated demyelination and inhibited glial activation and the production of tumor necrosis factor α (TNF-α) and interleukin 1β (IL-1β) without altering the number of olig2-positive cells. In vitro, RN-1734 treatment clearly inhibited the influx of calcium and decreased the levels of IL-1β and TNF-α in lipopolysaccharide (LPS)-activated microglial cells by suppressing NF-κB P65 phosphorylation. Apoptosis of oligodendrocyte induced by LPS-activated microglia was also alleviated by RN-1734. The results suggest that activation of TRPV4 in microglia is involved in oligodendrocyte apoptosis through the activation of the NF-κB signaling pathway, thus revealing a new mechanism of CNS demyelination.